Rasionalitas Calon DPR-RI I Ketut Kariyasa Adnyana Kepada Organisasi MGPSSR Buleleng Pada Pemilu Serentak 2019 - Stalin, Komang Gelen; Erawan, I Ketut Putra; Apriani, Kadek Dwita (Jurnal Nawala Politika; Vol 1 No 1 (2022): Jurnal Ilmu Politik 2022, 2022)
This study aims to analyze how candidate I Ketut Kariyasa Adnyana uses his rationality in boosting votes by cooperating with the MGPSSR organization as one of the factors that can win him in the 2019 Election to get votes. Phenomenon exploration is done by using rational choice theory from James S. Coleman (1990). The research method used is descriptive with a qualitative approach. The results of the study show that rational choice is closely related to Kariyasa Adnyana as a rational actor, ownership of the Buleleng MGPSSR resources, as well as public and organizational trust in supporting their political choices in the 2019 General Election. The main resources are the large human resources of Pasek itself and with the provision of assistance from I Ketut Kariyasa Adnyana can maintain and strengthen the rationality of both parties.